Un Estudio Descriptivo De Las Creencias Docentes Acerca Del Fenómeno Bullying - Kerman, Bernardo (European Scientific Journal, ESJ, 2016)
We present an ex post facto prospective single study group (Leon & Montero, 2007). Participants are 316 adults, primary school teachers of the Autonomous City of Buenos Aires of both sexes, with an age range between 18 and 42 years (M = 23.17, SD = 3.1). The main objective of the project is to analyze beliefs of teachers in primary and secondary schools about the causes of the bullying phenomenon, preventive measures and contingent actions for resolution. How teachers perceive students and their behaviors, is related to the strategies they use to manage their classrooms (Valdez Cuervo Estévez, Nenninger et al., 2013). A medium-term goal in an upcoming project is the design of prevention programs to change the way teachers perceive and act on the mentioned phenomenon. Partial results are described.